PENGARUH HARGA DAN KUALITAS PRODUK TERHADAP KEPUTUSAN PEMBELIAN KOSMETIK SKIN CARE DEWI PADA PT SARIDEWI NATURAL KOSMETIK DI JAKARTA UTARA - Nurfi, Afifah; Haryantini (Journal of Research and Publication Innovation, 2024)
This research aims to determine the influence of price and product quality on purchasing decisions at the Distributor PT Saridewi Natural Kosmetik. The design of this research is quantitative descriptive analysis. The population in this study were all consumers who had tried Dewi Skin Care products and the research sample consisted of 99 respondents. The sampling technique used is Probability Sampling with Random Sampling type. Data analysis methods use data instrument tests, classical assumption tests, simple linear regression tests & multiple linear regression, correlation tests, determination tests, hypothesis tests. The research results show that Price (X1), Product Quality (X2), simultaneously have a significant effect on Purchasing Decisions (Y) seen from the hypothesis test, the t value obtained > t table or (15.818 > 1.996). This is also reinforced by the value ̀ρ value < Sig.0.05 or (0.000 < 0.005). Thus, Ho is rejected and Ha is accepted. Partially Price (X1) has a significant effect on Purchasing Decisions (Y) and Product Quality (X2) has a partially significant effect on Purchasing Decisions (Y) seen from the hypothesis test, the calculated t value > t table or (3.026 > 1.996). This is also reinforced by the ρ value < Sig.0.05 or (0.004 < 0.005). Thus, Ho is rejected and Ha is accepted. Hypothesis testing obtained a value of Fcount > Ftable or (192.183 > 3.14), this was also confirmed by a ρ value < Sig.0.05 or (0.000 < 0.05). Thus, Ho is rejected and Ha is accepted. Therefore, there is a simultaneous influence between price and product quality on purchasing decisions.